2012
DOI: 10.1021/am3016203
|View full text |Cite
|
Sign up to set email alerts
|

Preferentially Grown Ultranano c-Diamond and n-Diamond Grains on Silicon Nanoneedles from Energetic Species with Enhanced Field-Emission Properties

Abstract: The design and fabrication of well-defined nanostructures have great importance in nanoelectronics. Here we report the precise growth of sub-2 nm (c-diamond) and above 5 nm (n-diamond) size diamond grains from energetic species (chemical vapor deposition process) at low growth temperature of about 460 °C. We demonstrate that a pre-nucleation induced interface can be accounted for the growth of c-diamond or n-diamond grains on Si-nanoneedles (Si-NN). These preferentially grown allotropic forms of diamond on Si-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 45 publications
1
11
2
Order By: Relevance
“…These β values are superior to those reported by Thomas et al 26 and much higher than values reported by Tzeng et al 25,33 whose field emission results and analysis appear to have internal contradictions. Two emission regimes can be distinguished.…”
Section: Resultscontrasting
confidence: 80%
“…These β values are superior to those reported by Thomas et al 26 and much higher than values reported by Tzeng et al 25,33 whose field emission results and analysis appear to have internal contradictions. Two emission regimes can be distinguished.…”
Section: Resultscontrasting
confidence: 80%
“…On the other hand, Si nanocones fabricated by Shang et al exhibit a turn-on field of 13 V μm –1 , although the current density is higher (200 μA cm –2 ) compared to the present case . Likewise, Thomas et al reported on FE from Si nanoneedles having a turn-on field of 5.3 V μm –1 and current density of 400 μA cm –2 . Thus, a wide range of figure of merits (e.g., turn-on field and current densities) exist in the literature.…”
Section: Resultsmentioning
confidence: 47%
“…On lowering the a‐C layer at interface UNCD/Au‐Si, composite structure delivers better conductivity and improves EFE . Precise growth of sub‐2 nm/above 5 nm sized diamond grains is achieved due to energetic species under low growth temperature and prenucleated interface, thus, tiny grains on silicon nanoneedles deliver enhanced EFE . Gold‐UNCD films show superior EFE properties than copper‐UNCD films and the authentic factor underneath the mechanism is the presence of nanographitic phases .…”
Section: Introductionmentioning
confidence: 99%